2005
DOI: 10.1093/nar/gni051
|View full text |Cite
|
Sign up to set email alerts
|

Conditional and inducible transgene expression in mice through the combinatorial use of Cre-mediated recombination and tetracycline induction

Abstract: Here we describe a triple transgenic mouse system, which combines the tissue specificity of any Cre-transgenic line with the inducibility of the reverse tetracycline transactivator (rtTA)/tetracycline-responsive element (tet-O)-driven transgenes. To ensure reliable rtTA expression in a broad range of cell types, we have targeted the rtTA transgene into the ROSA26 locus. The rtTA expression, however, is conditional to a Cre recombinase-mediated excision of a STOP region from the ROSA26 locus. We demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
220
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(227 citation statements)
references
References 41 publications
(39 reference statements)
1
220
1
Order By: Relevance
“…The number of capillaries correlated with the number of proliferating hepatocytes (PCNA positive nuclei) and the expression levels of hVEGF-A 165 (Figure 4D). Similar results have been seen in transgenic mice which express hVEGF-A 165 in the liver [18], [29][30].…”
Section: Resultssupporting
confidence: 84%
“…The number of capillaries correlated with the number of proliferating hepatocytes (PCNA positive nuclei) and the expression levels of hVEGF-A 165 (Figure 4D). Similar results have been seen in transgenic mice which express hVEGF-A 165 in the liver [18], [29][30].…”
Section: Resultssupporting
confidence: 84%
“…Uncontrolled transgenic expression of a given gene typically leads to embryonic lethality that precludes further studies in adults [32]. For instance, a Gpr124 conditional knockout in the endothelia of adult mice resulted in BBB leakage in mouse models of both ischemic injury and glioblastoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…Eremina et al [8] have shown that unrestricted expression of VEGF 165 during development is significantly detrimental, which taken together with these results suggest a balance of pro-angiogenic/anti-angiogenic VEGF-A is required for normal development and function [8, 9, 31, 45, 46]. Expression of VEGF xxx b isoforms and crucially the control of distal and proximal 3′-end splicing control during kidney development may therefore play a significant role in the modulation of VEGF xxx -driven responses.…”
Section: Discussionmentioning
confidence: 99%